PENGARUH NUGGET IKAN BILIS (Mystacoleucus Padangensis) TERHADAP KENAIKAN BERAT BADAN PADA BATITA - Febriniwati Rifdi; Fatkhurohmah Candra Rahayu (Universitas Fort de Kock Bukittinggi, 2022)
At the age of Under Three Years(BATITA), the child's height increases by 9 cm and his weight increases by about 2 kg. However, the need for calories is actually increasing due to increased physical activity. Likewise with the nutritional needs to support the immune system because BATITA have started to actively explore. The purpose of this study was to see the effect of Bilis Fish Nugget on BATITA Weight Gain in the Working Area of Kota BesarCommunity Health Center, Dhamasraya Regency in 2022. This research method was quasi-experimental. The study was conducted on 5 children who met the criteria. The measuring instrument used in this study was an observation sheet and weight loss using univariate and bivariate analysis. This research was conducted in August 2022. The results obtained that the average body weight before administration of Bilis Fish Nugget was 13.54 kg, after giving Bilis Fish Nugget the average body weight was 13.82 kg with a mean difference of 0.28 and with a value of p = p = 0, 45 < 0.05. Based on the results above, it can be concluded that there is an effect of Bilis Fish Nugget with increasing BATITA body weight, so it is recommended to the Community Health Centerto always make new innovations in giving supplementary feedingso that the supplementary feedingprogram is not only in the form of biscuits to increase children's weight and growth of BATITA